Plasma- and Saliva Exosome Profile Reveals a Distinct MicroRNA Signature in Chronic Periodontitis - Nik Mohamed Kamal, Nik Nur Syazana; Awang, Raja Azman Raja; Mohamad, Suharni; Shahidan, Wan Nazatul Shima (Frontiers in Physiology, 2020)
Chronic periodontitis (CP) is an oral cavity disease arising from chronic inflammation of the periodontal tissues. Exosomes are lipid vesicles that are enriched in specific microRNAs (miRNAs), potentially providing a disease-specific diagnostic signature. To assess the value of exosomal miRNAs as biomarkers for CP, 8 plasma- and 8 salivary-exosomal miRNAs samples were profiled using Agilent platform (comparative study). From 2,549 probed miRNAs, 33 miRNAs were significantly down-regulated in CP as compared to healthy plasma samples. Whereas, 1,995 miRNAs (1,985 down-regulated and 10 up-regulated) were differentially expressed in the CP as compared to healthy saliva samples. hsa-miR-let-7d [FC=-26.76; AUC=1; r=-0.728 [p-value=0.04]), hsa-miR-126-3p (FC=-24.02; AUC=1; r=-0.723 [p-value=0.043]) and hsa-miR-199a-3p (FC=-22.94; AUC=1; r=-0.731 [p-value=0.039]) are worth to be furthered studied for plasma-exosomal samples. Meanwhile, for salivary-exosomal samples, hsa-miR-125a-3p (FC=2.03; AUC=1; r= 0.91 [p-value=0.02]) is worth to be furthered studied. These miRNAs are the reliable candidates for the development of periodontitis biomarker, as they were significantly expressed differently between CP and healthy samples, have a good discriminatory value and strongly correlate with the mean of PPD.hsa-miR-6821-5p, hsa-miR-4485-5p, hsa-miR-6088, hsa-miR-103a-3p, hsa-let-7d-5p, hsa-miR-126-3p, hsa-miR-199a-3p and hsa-miR-150-5p were found to down-regulated in both plasma and saliva samples indicating that they could be involved in the progression of CP disease. These findings highlight the potential of exosomal miRNAs profiling in the diagnosis from both sourced as well as provide new insights into the molecular mechanisms involved in CP.